2018
DOI: 10.24263/2304-974x-2018-7-4-17
|View full text |Cite
|
Sign up to set email alerts
|

Thermal destruction kinetics of coal and solid biomass mixtures

Abstract: Introduction. The work deals with the research on the kinetics of constituent stages of the combustion process of biomass as an individual fuel and as blends with low reactive anthracite coal from the Donetsk Coal Basin. Materials and methods. The samples of biomass (including the wastes of agricultural and food industries) and Ukrainian from the coal Donetsk Basin were studied by means of nonisothermal TGA. Kinetic studies of the samples was carried out on the Paulik-Paulik-Erdei Q-1000 system derivatograph w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In studies into pellet burning, two approaches can be identified: (1) crushing pellets to small (thermally thin) particles and thermogravimetric study of their thermal destruction and carbon burnout at a relatively slow heating rate [8]; such studies were carried out as to the torch [9,10] or fluidised bed burning [11]; (2) study into thermal destruction and carbon burnout from larger particles and whole pellets (thermally thick particles) relating to their burning in a fixed fuel bed [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In studies into pellet burning, two approaches can be identified: (1) crushing pellets to small (thermally thin) particles and thermogravimetric study of their thermal destruction and carbon burnout at a relatively slow heating rate [8]; such studies were carried out as to the torch [9,10] or fluidised bed burning [11]; (2) study into thermal destruction and carbon burnout from larger particles and whole pellets (thermally thick particles) relating to their burning in a fixed fuel bed [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%